2008
DOI: 10.1080/00291950802335475
|View full text |Cite
|
Sign up to set email alerts
|

It is all about livelihoods: A study of women working in stone chip production in Cape Coast Municipality, Ghana

Abstract: Outcrops of granite in several localities in the urban and peri-urban fringes of Cape Coast Municipality in Ghana have led to stone chip production becoming a major livelihood strategy for vulnerable and poor women. Previously, this work was primarily carried out by men, but today female workers dominate the workforce, and increasingly it is seen as a way for women to seek a viable living in conditions which are otherwise marginalized and poor in economic terms. The demand for stone chips has increased with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…CCTH is located in Cape Coast (population approximately 170,000), which is the smallest district in Ghana in terms of land size, the poorest in Central Region, and the fourth poorest region in Ghana. [ 9 , 10 ] It serves as the main referral hospital for most of the rural Central and parts of Western regions of Ghana. The hospital also serves as the teaching hospital of the University of Cape Coast, School of Medical Sciences (UCC-SMS).…”
Section: Methodsmentioning
confidence: 99%
“…CCTH is located in Cape Coast (population approximately 170,000), which is the smallest district in Ghana in terms of land size, the poorest in Central Region, and the fourth poorest region in Ghana. [ 9 , 10 ] It serves as the main referral hospital for most of the rural Central and parts of Western regions of Ghana. The hospital also serves as the teaching hospital of the University of Cape Coast, School of Medical Sciences (UCC-SMS).…”
Section: Methodsmentioning
confidence: 99%
“…The concept of livelihood has been developing since the 1990s (Lund et al, 2008). This concept initially developed in England but was later designed in such a way that it is very relevant for developing regions (Ellis, 2000).…”
Section: Literature Review Livelihood Conceptmentioning
confidence: 99%
“…Correspondingly, Ellis (2000) defines livelihood as assets, activities, and access, which together determine the life obtained by individuals or households (Ellis, 2000;Allison & Ellis, 2001;Ellis & Bahiigwa, 2003;Ellis & Mdoe, 2003). The concept of livelihood recognizes five main asset categories which include: 1) natural capital, consisting of land, water, wildlife, biodiversity, environmental resources, and others; 2) Social capital, consisting of networks, group membership, trust relationships, community institutional access; 3) human capital, including skills, knowledge, ability to work, and good health; 4) physical capital, in the form of necessary infrastructures, such as transportation, water, energy, and communication; 5) financial capital, in the form of financial resources owned by everyone, such as savings, availability of credit, regular remittances, or pension funds (Allison & Ellis, 2001;Lund et al, 2008). Furthermore, Yeboah (2010) adds political capital as one of the livelihood assets, in addition to the assets described above, so that assets or capital as livelihood resources are divided into six categories.…”
Section: Literature Review Livelihood Conceptmentioning
confidence: 99%
“…Lund et al (2008) studied female stone cutters in the Cape Coast District in the central Region, who were living in an urban or peri-urban environment in one of the regions in Ghana with the highest poverty percentages. Applying a related livelihoods approach, the authors showed how a relatively poor group of women, female stone cutters working in a vulnerable and disempowered context carve out a living based on hard work and selforganisation with relatively marginalised and depleting resources.…”
Section: The Urban Poormentioning
confidence: 99%